Improving Purchasing Decisions with the Role of Product and Price Combinations - Hendratmoko, Hendratmoko; Vita, Elisabeth; Sitorus, Arjuna Candra; Harun, Mohd Zainal Munshid (Jurnal Manajemen, 2024)
Products that precisely meet consumer needs have a greater potential for acceptance. Likewise, products that align with consumer preferences stand a chance of being embraced by consumers. The appropriate pricing exerts an influence on consumer decisions when making purchases. This study aims to delve deeper into the impact of product and price combinations on purchasing decisions. Employing quantitative methods, this research involved 124 respondents, all located in Jakarta. Data analysis was conducted using SPSS 29. The findings of this study underscore the positive and significant influence of both product and price variables on purchasing decisions. Additionally, it highlights the importance of combining product and price to enhance the likelihood of purchase decisions. Contrary to the assumed linear relationship, this study reveals a non-linear combination between product and price. The significance of this research lies in uncovering the non-linear relationship between product and price and its impact on purchasing decisions. It challenges the notion that good product quality always comes at a high price, suggesting otherwise.